Obtaining a lower estimate of the fatigue limit of metals by a simplified quantitative thermometric approach in a low-cost one-specimen test. (June 2022) - Schaefer, Florian; Rosar, Jan; Wu, Haoran; Starke, Peter; Marx, Michael
Abstract: The plasticity of metals leads to an internal heat generation during fatigue testing. Therefore, qualitative and quantitative thermography are widely accepted for assessing fatigue damage. The onset of significant heat generation and temperature rise is usually attributed to the fatigue limit of a material. Now, a 40-year-old but just rarely used measurement technique using NTC thermistors is used to reveal the temperature profile in a specimen. A direct comparison with modern thermographic methods exposes the much higher resolution of this simple and inexpensive method. This method provides the much desired ability to assess fatigue limit rapidly and efficiently with only one specimen, even for homogeneous materials and materials conditions with high thermal conductivity or even for small specimen volumes, in a valid and very reliable manner. Graphical abstract: Highlights: Quantitative thermometry is a simple technique for fatigue limit determination. Fatigue limit estimate benefits from higher resolution of NTCs. Quantitative thermometry even for small specimens and for high thermal conductivity. Measurement of heat generation gives lower estimate for fatigue limit.